PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. ES KOPI SURYA PLASCUP DI KOTA TANGERANG SELATAN - Achmad Muzizaturrohim; Rissa Hanny (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The purpose of this study is to determine the Price Variable (X1), Product Quality (X2), Purchasing Decision (Y), and the Influence of Price and Product Quality on Purchasing Decisions at PT. Es Kopi Surya Plascup in South Tangerang City. This research method uses a quantitative method with a descriptive approach and the population in this study is 2,120 consumers. The sample used in this study uses the entire population of 96 consumers as respondents. In this study the sampling technique used is nonprobability sampling. The results of the Promotion variable have a significant effect on Purchasing Decisions with a calculated t value of 7.974> t table 1.661 and a sig. value of 0.000 <0.05 The results of the Product Quality variable significantly influence Purchasing Decisions with a calculated t value of 8.081> t table 1.660 and a sig. value. of 0.000 < 0.05 The results of the Price and Product Quality variables simultaneously have a significant effect on Purchasing Decisions with a calculated f value of 38.194 > f table 3.095 and a sig value of 0.000 < 0.5.